Evaluation of knowledge about gestational diabetes among doctors and nurses in primary care services in Cascavel-PR (Research, Society and Development, 2023)
Gestational Diabetes Melittus (GDM) is a very common metabolic problem in pregnancy. Whereas pregnancies complicated by diabetes present an increased risk of unfavorable perinatal outcomes and the Brazilian challenge to reduce the neonatal component of infant mortality, demonstrated the need for a correct and early screening of this pathology. The obstetrician gynecologist, general practitioner and nurses who care for pregnant women in primary care services are essential agents for this purpose, and need to be familiar with current protocols. This study aimed to evaluate the knowledge of doctors and nurses in the Primary Care Services in the city of Cascavel-PR on the screening of Gestational Diabetes according to the new protocols, since gestational diabetes is a disease with high prevalence and often underdiagnosed. The study has descriptive character, exploratory with quantitative approach carried out by application and analysis of structured questionnaire and previously validated. It was demonstrated that doctors and nurses who work in Primary Care of Cascavel-PR have a relatively good success rate to the questions applied about the diagnosis of gestational diabetes. However, ideally, a higher success rate would be satisfactory, ensuring that every pregnant woman had a correct and accurate diagnosis as early as possible.